Assessing competencies in rheumatology. Issue 1 (30th September 2004) - Dacre, J; Haq, I
Abstract : Assessment of competencies in rheumatology is difficult, but possible, and is an important part of the evaluation of practising clinicians, helping to prevent poor performance. Competencies are currently assessed by the Royal College of Physicians, the General Medical Council, and the National Clinical Assessment Authority.